Gramsci and Labor as a Foundation for Hegemony - Del Roio, Marcos [UNESP] (My University, 2022)
The hegemony category is one of the keys to entering the complex universe that Gramsci builds in Prison Notebooks, although not the only one. In fact, the increased concern with this category only became more intense in the 70s, when the “Eurocommunist” strategy of disputing the state through bourgeois democracy was anticipated and the so-called critical edition of Prison Notebooks was being prepared.